PENANGANAN PEMERINTAH DALAM MENGATASI ANAK PUTUS SEKOLAH DI KOTA MAKASSAR - Natsir, Nasrah (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
This research aims to describe: The government's handling of out-of-school children in Makassar City. This research uses a qualitative approach with a case study type of research. The subject of this research is the head of the Makassar City education department, while the object of this research is the government's handling of out-of-school children by the Makassar City education department. Data collection was carried out using interview, observation and documentation data procedures. Techniques used in data analysis are data collection, data reduction, data presentation. The triangulation used is to explain the validity of the data using source triangulation and technical triangulation. Based on the research results, it shows that the government's role in dealing with out-of-school children includes government management and government efforts in dealing with out-of-school children in the city of Makassar. As we know, the condition of children who have dropped out of school really needs education and motivation. So that from these results they have knowledge about education and skills.